A Comparison between the Brand Personality Construct of KFC and Marrybrown: Their Restaurant Concept and Brand Preference - Lim, Kuang Long (2005)
This dissertation undertakes the research project from a deductive position based on Aaker’s (1997) brand personality to shape the result by adopting the quantitative research process. Brand personality scale measures important aspects of the personalities that consumers attribute to brands of all kinds. Marketers and researchers have embraced brand personality as an important facet of brand management and a key source of brand differentiation (Siguaw et. al., 1999). This paper attempts to measure how restaurant concept suggested by Walker and Lundberg (2005), influences brand personality. This in turn, investigates how brand personality affects restaurant brand preference. KFC, the largest foreign fast food chain, and Marrybrown, the largest local fast food chain, are chosen to measure restaurant personality by using 42 traits Brand Personality Scale developed by Aaker (1997) and 19 restaurant concept items by Walker and Lundberg (2005). The findings show that different restaurant concept elements influence different brand personality dimensions, and these different brand personality dimensions in turn, affect the brand preference. This dissertation also provides empirical evidence regarding the extent to which local and foreign restaurant brands have established clear and distinct brand personalities in the minds of consumers. Overall, KFC brand has proved to be more preferable compared to Marrybrown.